Buku Cerita Bergambar Tentang Cerita Perjuangan Tokoh Ken Umang Sebagai Media Informasi: Buku Cerita Bergambar Tentang Cerita Perjuangan Tokoh Ken Umang Sebagai Media Informasi - Andi Dwi Payana Putra; Faldi Hendrawan (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2023)
Indonesia has cultural and historical diversity, one of which is from the Singasari Kingdom. Historical stories about the Singasari Kingdom until now are quite well known, namely about Ken Arok and Ken Dedes, only those who are better known in the historical stories of the Singasari Kingdom are these two figures, even though there are also other characters, one of which is Ken Umang, Ken Umang is a the second wife of Ken Arok, but this character is still not widely recognized by the public due to limited sources of this character. The solution offered in this research is a picture story book as a medium of information for Ken Umang's character. Where a picture story book is a book that displays a story supported by an image, so that readers can better appreciate the story presented.The results of testing with the questionnaire method in this study, showed that of 30 respondents agreed with the making of the Picture Story Book media which was able to introduce Ken Umang's character through the media.